AUDITORY PERFORMANCES AND SPEECH PRODUCTION OUTCOMES IN COCHLEAR IMPLANTED CHILDREN - VIOLETA NECULA; LAURA CÎMPEAN; MARCEL COSGAREA; ALINA BOCA; DORINA CHIRA; BIANCA NISTOR (Studia Universitatis Babes-Bolyai, 2011)
ABSTRACT. Auditory Performances and Speech Production Outcomes in Cochlear Implanted Children Introduction: Cochlear implantation is a well established treatment option in bilateral severe to profound hearing impaired children who received limited or no benefits from hearing aids. For parents, clinicians and speech therapist(s) the main goal after cochlear implantation is to develop the children's auditory perception and all the skills needed to communicate through spoken language. Material, Methods: We assessed 50 cochlear implanted children using pure tone audiogram for hearing level and global assessment scores like Revised Categories of Auditory Performance and Speech Intelligibility Scale for speech perception and production. We have included in our study only the pre/perilingual patients with minimum 6 months of cochlear implant use. All patients were implanted unilaterally with MedEl devices. The group was split into two groups according to the implantation age, G1, group of children implanted under the age of 5 years, and G2, group of children implanted over the age of 5. Results: After one and a half year of implant use and fitting sessions, most of the patients have had good hearing levels, they reached the 20-25 dB pure tone threshold. The auditory performance was improving permanently after the implant activation. The younger patients had small scores at the beginning but they progressed faster than the older ones. According to estimates, children implanted under the age of 5 years could have an intelligible conversation with a familiar person, about 2 years after implantation and around three years began to speak in order to be understood, perhaps with some difficulty, by people less familiar with their speech. Children implanted after the age of 5 had a slower evolution, they could understand a simple conversation with a familiar person after 2 ½ years of implant use and only after 4-5 years some of them could have a phone conversation. Discussions: Pure tone audiometry is a valuable indicator of cochlear implant functionality and helps adjust the speech processor parameters for a satisfactory threshold on each frequency. Speech and language development is a slow process, both for toddlers and older children. The speech production is a slower process and needs a lot of training with professional speech therapists. The younger children will perform better than the older children who needs more time to reach the maximum level. Conclusions: Speech development, the most important but the most difficult stage, involves an intensive auditory-verbal training, conducted by qualified persons, training which has to be continued at home, by the family, continuously stimulating the child, motivating him, with a strong effort from all of those who are around the child in order to achieve the best results.